Relation of war experiences, posttraumatic reactions and depression symptoms among children. - Jelić, Margareta (2002)
This paper studies the relationship between stressful experiences caused by the war, symptoms of depression and posttraumatic stress reactions in children. Researches in this area suggest moderate correlations between the number of war experiences and posttraumatic stress reactions. However, there is no clear data on how long those reactions last after the war is over. We conducted this research six years after the war, in order to investigate whether war experiences had left consequences in form of posttraumatic stress reactions and symptoms of depression. Our research was conducted in Hrvatska Kostajnica, a small town that was totally destroyed during the war, and whose inhabitants became refugees. The questionnaires were administered to 243 pupils, both girls and boys, who attended primary school in Hrvatska Kostajnica. The questionnaire consisted of Stressful War Experiences Inventory (RSTI), Posttraumatic Stress Reactions Scale (PTSR) and Child Depression Inventory (CDI). The analyses indicate moderate correlation between the number of war experiences and posttraumatic stress reactions even after a period of six years after the war (r= .34), and low correlations between the number of war experiences and symptoms of depression (r= .14). The results were analyzed with regards to war traumatization, as well as many consequences of the war that still have a bad effect on the recovery of children. The results also indicate that girls have more posttraumatic stress reactions than boys. No differences between sexes were found on Child Depression Inventory.
Projekt MZOS
ENG